Landscape of mutations in early stage primary cutaneous melanoma: An InterMEL study. (12th August 2022) - Luo, Li; Shen, Ronglai; Arora, Arshi; Orlow, Irene; Busam, Klaus J.; Lezcano, Cecilia; Lee, Tim K.; Hernando, Eva; Gorlov, Ivan; Amos, Christopher; Ernstoff, Marc S.; Seshan, Venkatraman E.; et al.
Abstract: It is unclear why some melanomas aggressively metastasize while others remain indolent. Available studies employing multi‐omic profiling of melanomas are based on large primary or metastatic tumors. We examine the genomic landscape of early‐stage melanomas diagnosed prior to the modern era of immunological treatments. Untreated cases with Stage II/III cutaneous melanoma were identified from institutions throughout the United States, Australia and Spain. FFPE tumor sections were profiled for mutation, methylation and microRNAs. Preliminary results from mutation profiling and clinical pathologic correlates show the distribution of four driver mutation sub‐types: 31% BRAF; 18% NRAS; 21% NF1; 26% Triple Wild Type. BRAF mutant tumors had younger age at diagnosis, more associated nevi, more tumor infiltrating lymphocytes, and fewer thick tumors although at generally more advanced stage. NF1 mutant tumors were frequent on the head/neck in older patients with severe solar elastosis, thicker tumors but in earlier stages. Triple Wild Type tumors were predominantly male, frequently on the leg, with more perineural invasion. Mutations in TERT, TP53, CDKN2A and ARID2 were observed often, with TP53 mutations occurring particularly frequently in the NF1 sub‐type. The InterMEL study will provide the most extensive multi‐omic profiling of early‐stage melanoma to date. Initial results demonstrate a nuanced understanding of the mutational and clinicopathological landscape of these early‐stage tumors.